Differential patterning of genes involved in serotonin metabolism and transport in extra-embryonic tissues of the mouse. (June 2016) - Wu, Hsiao-Huei; Choi, Sera; Levitt, Pat
Abstract: Introduction: Serotonin (5-HT) is an important neuromodulator, but recently has been shown to be involved in neurodevelopment. Although previous studies have demonstrated that the placenta is a major source of forebrain 5-HT during early forebrain development, the processes of how 5-HT production, metabolism, and transport from placenta to fetus are regulated are unknown. As an initial step in determining the mechanisms involved, we investigated the expression patterns of genes critical for 5-HT system function in mouse extraembryonic tissues. Methods: Mid-through late gestation expression of 5-HT system-related enzymes, Tph1, Ddc, Maoa, and 5-HT transporters, Sert/Slc6a4, Oct3 / Slc22a3, Vmat2 / Slc18a2, and 5-HT in placenta and yolk sac were examined, with cell type-specific resolution, using multiplex fluorescent in situ hybridization to co-localize transcripts and immunocytochemistry to co-localize the corresponding proteins and neurotransmitter. Results: Tph1 and Ddc are found in the syncytiotrophoblast I (SynT-I) and sinusoidal trophoblast giant cells (S-TGC), whereas Maoa is expressed in SynT-I, syncytiotrophoblast II (SynT-II) and S-TGC. Oct3 expression is observed in the SynT-II only, while Vmat2 is mainly expressed in S-TGC. Surprisingly, there were comparatively high expression of Tph1, Ddc, and Maoa in the yolk sac visceral endoderm. Discussion: In addition to trophoblast cells, visceral endoderm cells in the yolk sac may contribute to fetal 5-HT production. The findings raise the possibility of a more complex regulation of 5-HT access to the fetus through the differential roles of trophoblasts that surround maternal and fetal blood space and of yolk sac endoderm prior to normal degeneration. Highlights: Tph1 and Ddc are mainly expressed by syncytiotrophoblast I and sinusoidal trophoblast giant cells. Maoa is expressed in both syncytiotrophoblast I and II, as well as in sinusoidal trophoblast giant cells. Oct3 is expressed in syncytiotrophoblast II only. Vmat2 is mainly expressed in sinusoidal trophoblast giant cells. Tph1, Ddc, and Maoa are expressed in the yolk sac visceral endoderm.